A comparison of the match demands of international and provincial rugby sevens - Ross, A.; Gill, N. D.; Cronin, J. B. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To compare the running demands and match activity profiles of international and provincial rugby sevens players. Participants: 84 rugby sevens players, consisting of 16 international players from 1 team and 68 provincial players from 8 teams. Methods: Global positioning system analysis was completed during international and provincial tournament matches. Video analysis was also used to quantify the individual match activities during tournament matches. Results: Trivial to moderate differences were found in the running demands of international and provincial players, with internationals covering a greater distance at very high speed (ES = 0.30) and performing a greater number of sprints (ES = 0.80). Small differences were found between the 2 levels in all but total tackles (ES = 0.07) and defensive ruck effectiveness (ES = 0.64). International matches incurred a greater overall ball-in-play time than provincial matches (proportion ratio = 1.32). Conclusions: These findings demonstrate that both physical and technical factors distinguish international and provincial rugby sevens, although overall match demands are similar.